2001
DOI: 10.1159/000050096
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum Reduces Infection of Pancreatic Necrosis in Experimental Acute Pancreatitis

Abstract: Background: Infection is the commonest cause of death in acute pancreatitis. Early reduction of commensal flora (particularly Lactobacillus species) and, at the same time, overgrowth of Enterobacteriaceae, especially Escherichia coli, have recently been described during acute pancreatitis. Lactobacillus plantarum has been shown to be effective in reducing the egress of endotoxin and microbial translocation in several experimental models such as chemically induced hepatitis and ulcerative colitis. Aim: The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 12 publications
1
30
0
2
Order By: Relevance
“…Oláh et al (2002a) reported that when patients with acute pancreatitis received Lactobacillus plantarum 299, they had lower incidence of pancreatic sepsis and needed less surgical interventions compared with control patients. It was also reported that the treatment with probiotics was effective in reducing microbacterial translocation in an experimental pancreatitis model (Mangiante et al, 2001). The rate of bacterial translocation was also affected by administration of probiotics in experimental acute pancreatitis in our study.…”
Section: Discussionsupporting
confidence: 79%
“…Oláh et al (2002a) reported that when patients with acute pancreatitis received Lactobacillus plantarum 299, they had lower incidence of pancreatic sepsis and needed less surgical interventions compared with control patients. It was also reported that the treatment with probiotics was effective in reducing microbacterial translocation in an experimental pancreatitis model (Mangiante et al, 2001). The rate of bacterial translocation was also affected by administration of probiotics in experimental acute pancreatitis in our study.…”
Section: Discussionsupporting
confidence: 79%
“…So another method using probiotics has been proposed to reduce the infection of necrosis by intestinal bacteria. One experimental study is effective in reducing microbial translocation in pancreatitis [24]. The studies of Oláh et al 2002 [14] and Oláh et al 2007 [16] found enteral feeding with probiotic was effective in reducing infections and mortality, as well as reducing the number of surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that the instillation of SCFAs orally or rectally stimulated gut epithelial cell proliferation (36). Results from a previous study showed that L. plantarum DSM 9843 is effective in preventing microbial translocation in experimental pancreatitis (37,38). Recent data demonstrated that pretreatment with L. plantarum protects against Escherichia coli -induced increase in intestinal permeability (39).…”
Section: Discussionmentioning
confidence: 99%